2013
DOI: 10.1002/chem.201301735
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoclusters Confined in a Supercage of Y Zeolite for Aerobic Oxidation of HMF under Mild Conditions

Abstract: Au nanoclusters with an average size of approximately 1 nm size supported on HY zeolite exhibit a superior catalytic performance for the selective oxidation of 5‐hydroxymethyl‐2‐furfural (HMF) into 2,5‐furandicarboxylic acid (FDCA). It achieved >99 % yield of 2,5‐furandicarboxylic acid in water under mild conditions (60 °C, 0.3 MPa oxygen), which is much higher than that of Au supported on metal oxides/hydroxide (TiO2, CeO2, and Mg(OH)2) and channel‐type zeolites (ZSM‐5 and H‐MOR). Detailed characterizations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(119 citation statements)
references
References 70 publications
3
104
0
5
Order By: Relevance
“…The basic medium provides higher reaction rates and, in the majority of cases, is essential to get a high catalytic activity. However, the basic medium also favors HMF degradation and requires a final neutralization step, which is not desirable from the environmental and Au-based catalysts have been reported to perform this reaction in water and in the presence of an excess of base with high yields of FDCA [56][57][58][59][60][61]. Au-containing bimetallic catalysts were developed in order to improve the catalytic performance, but required the use of a homogenous base [33,58,[62][63][64][65][66][67].…”
Section: Base-free 5-hydroxymethylfurfural Oxidationmentioning
confidence: 99%
“…The basic medium provides higher reaction rates and, in the majority of cases, is essential to get a high catalytic activity. However, the basic medium also favors HMF degradation and requires a final neutralization step, which is not desirable from the environmental and Au-based catalysts have been reported to perform this reaction in water and in the presence of an excess of base with high yields of FDCA [56][57][58][59][60][61]. Au-containing bimetallic catalysts were developed in order to improve the catalytic performance, but required the use of a homogenous base [33,58,[62][63][64][65][66][67].…”
Section: Base-free 5-hydroxymethylfurfural Oxidationmentioning
confidence: 99%
“…Many researchers have focused their attention on the study of the best material and reaction conditions for improving FDCA yield [14][15][16][17]. So far, catalyst stability and productivity are low, but the possibility to obtain both high product purity and better process sustainability makes this catalyst type highly interesting.…”
Section: Introductionmentioning
confidence: 99%
“…The literature survey for the oxidation of HMF to FDCA indicated that this reaction has been performed using stoichiometric amounts of oxidants and expensive catalytic systems containing noble metals such as Pt [17][18][19][20][21][22], Pd [23][24][25][26], Au [27][28][29][30][31][32], Ru [33], or their alloys [34][35][36][37][38][39][40][41]. In addition, the presence of a base is crucial in order to facilitate the desorption of the resulted acid from the catalytic surface.…”
Section: Introductionmentioning
confidence: 99%